From natural gas to hydrogen: Climate impacts of current and future gas transmission networks in Germany - Jülich, Alexander; Blum, Maximilian; Zelt, Ole; Viebahn, Peter (Frontiers in Energy Research, 2025)
Hydrogen emissions arise from leakage during its production, transport, storage and use, leading to an increase in atmospheric hydrogen concentrations. These emissions also cause an indirect climate effect, which has been quantified in the literature with a global warming potential over 100 years (GWP100) of about 11.6, placing hydrogen between carbon dioxide (1) and methane (29.8). There is increasing debate about the climate impact of an energy transition based on hydrogen. As a case study, we have therefore evaluated the expected climate impact of switching from the long-distance natural gas transmission network to the outlined future “hydrogen core network” in Germany. Our analysis focuses on the relevant sources and network components of emissions. Our results show that the emissions from the network itself represent only about 1.8% of total emissions from the transmission of hydrogen, with 98% attributed to energy-related compressor emissions and only 2% to fugitive and operational hydrogen leakage. Compared to the current natural gas transmission network, we calculate a 99% reduction in total network emissions and a 97% reduction in specific emissions per transported unit of energy. In the discussion, we show that when considering the entire life cycle, which also includes emissions from the upstream and end-use phases, the switch to hydrogen reduces the overall climate impact by almost 90%. However, while our results show a significantly lower climate impact of hydrogen compared to natural gas, minimising any remaining emissions remains crucial to achieve carbon neutrality by 2045, as set in Germany’s Federal Climate Action Act. Hence, we recommend further reducing the emissions intensity of hydrogen supply and minimising the indirect emissions associated with the energy supply of compressors.